2017
DOI: 10.1002/cjce.22790
|View full text |Cite
|
Sign up to set email alerts
|

Modelling, simulation, and membrane wetting estimation in gas‐liquid contacting processes

Abstract: A set of experiments for CO 2 separation from CO 2 -N 2 mixture by absorption into water by means of a gas-liquid membrane contacting process is modelled using the mass continuity equation by combining process conditions, membrane and fluids properties, and module geometric characteristics. The general case of non-constant concentration of the diffusing component in the shell side (Case B) is used, which entails an integro-differential boundary condition at the lumen-wall. The computational method is compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(27 citation statements)
references
References 101 publications
3
24
0
Order By: Relevance
“…The authors showed that the computational wetting to match the experimental data decreases with the increase of the fiber-side liquid velocity, which indicates that an inverse relationship may exist between the liquid flow rate and the wetting, as also demonstrated by Pantoleontos et al in a previous study when considering a physical-absorption case. 8 The current study improves upon the previous work by Pantoleontos et al, who presented a CO 2 -in-water physicalabsorption case along with macroscopic mass balance on the shell side, also accounting for process conditions, membrane and fluid properties, and module geometric characteristics. 8 The ubiquitous resistance-in-series approach, as shown in eq 1, is a pertinent prerequisite in the analysis attempting to interpret the underlying wetting phenomena and aspiring to discern any wetting pattern.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…The authors showed that the computational wetting to match the experimental data decreases with the increase of the fiber-side liquid velocity, which indicates that an inverse relationship may exist between the liquid flow rate and the wetting, as also demonstrated by Pantoleontos et al in a previous study when considering a physical-absorption case. 8 The current study improves upon the previous work by Pantoleontos et al, who presented a CO 2 -in-water physicalabsorption case along with macroscopic mass balance on the shell side, also accounting for process conditions, membrane and fluid properties, and module geometric characteristics. 8 The ubiquitous resistance-in-series approach, as shown in eq 1, is a pertinent prerequisite in the analysis attempting to interpret the underlying wetting phenomena and aspiring to discern any wetting pattern.…”
Section: Introductionsupporting
confidence: 69%
“…CO 2 removal using membrane-based gas absorption and reaction is gaining attention as an alternative to well-established industrial gas-separation and reaction equipment, such as reactive-absorption columns, because of the high mass transfer area (known a priori ) of the membrane modules per unit volume, their modular design, and easy scale-up of the process. A membrane bundle containing hundreds of fibers is placed within the membrane module with a customizable length, and it may provide a modular solution for easy lab- and pilot-testing with a specific surface area in the range of 1500–7000 m 2 /m 3 compared to 100–800 m 2 /m 3 for conventional devices …”
Section: Introductionmentioning
confidence: 99%
“…The microstructure parameters of the membrane have a significant influence on the desulfurization effect of the membrane contactor . Meanwhile, there is also no validated accurate model for the simulation of mass transfer behavior in a multichannel membrane contactor; therefore, the design and optimization of membrane contactors are hindered. …”
Section: Introductionmentioning
confidence: 99%
“…2D models are typically used for this kind of approaches. They consider the fiber radial direction to describe mass transfer in the different phases and perform a numeric resolution considering a single fiber [20,27,28,[37][38][39][40][41].…”
mentioning
confidence: 99%